Diffusion of Covid-19 in the Northern Metropolis in Northeast Brazil: territorial dynamics and risks associated with Social Vulnerability - Davis Pereira de Paula; David Hélio Miranda de Medeiros; Eduardo Lacerda Barros; Renan Gonçalves Pinheiro Guerra; Jáder de Oliveira Santos; João Sérgio Queiroz Lima; Rafaela Martins Leite Monteiro (Sociedade & Natureza)
Throughout history, humankind has lived through many crises arising from pandemics, and it is currently in the midst of one. Coronavirus disease, caused by the severe acute respiratory syndrome coronavirus 2, is causing serious problems related to public health and socioeconomic status across the globe. Having started in Asia, the disease has already reached Europe, Africa, and more recently the Americas; hence, it is necessary to understand the context in which it spreads in regions that carry high risks associated with social vulnerability, as in the case of Latin America. Brazil is the South American country most affected by the pandemic—its first case was confirmed at the end of February 2020, and in less than two months, its total number of cases has already crossed 25,000. Among its worst-hit states, Ceará in Northeast Brazil worries health agencies as there have already been more than 2,000 cases in the 30 days of the outbreak in the state. Even more worrying is its capital Fortaleza, which has become the epicenter of the spread of the disease in Ceará, accounting for 86.5% cases and 67% deaths in the state—95% of the neighborhoods in Fortaleza have confirmed cases of the disease. An aspect that particularly causes concern is the disease’s diffusion, from neighborhoods with the highest family income to those with the lowest, directly affecting the socially vulnerable populations in territories with a majority of precarious settlements; in Fortaleza, favelas are the main type of precarious settlements (73.6%). The analyses presented as part of this research can assist in identifying priority areas for state intervention through family assistance resources.